Mariah Dalam Novel Terusir Karya Buya Hamka dengan Kajian Analisis Wacana Kritis Sara Mills - Juliana, S., Juliana; Charlina, Charlina; Burhanudin, Dudung (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
This research aims to describe the subject-object position and the writer-reader position regarding the position of women in the novel Terusir by Buya Hamka. This research is qualitative descriptive research. The subject position in this research is the author who tells the reader about a weak and deluded woman. The position of object of this research is the position of a character named Mariah who was divorced and thrown out by her husband because of slander from her husband's family, so she became a prostitute. The data for this research were obtained from an analysis of the novel published by Gema Insani in 2016. The results of this research show the position of a subject-object in the story, where women are weak objects have no power in the household, and are not strong enough to maintain their identity because conditions are increasingly cruel. Meanwhile, the subject position leads readers to sympathize with weak women who should be allowed to defend themselves from the slander they receive, so that they do not have to be divorced and thrown out by their husbands.